Adherence to Healthy Lifestyle and the Risk of Function Limitations in Late Life: The Atherosclerosis Risk in Communities Study - Li, Dongze; Jia, Yu; Yu, Jing; Liu, Yi; Li, Fanghui; Liu, Yanmei; Wu, Qinqin; Liao, Xiaoyang; Zeng, Zhi; Zeng, Rui; Wan, Zhi (Frontiers in Aging Neuroscience, 2021)
Background: Physiological function impairment is the main precursor of assisted living, movement disorder, and disability in the elderly. The relationship between a combination of healthy lifestyle factors and functional limitations is unclear. We investigated the association between healthy lifestyle scores and risk of functional impairment in community residents. Methods: A total of 10602 participants (aged 40–64 years) of the Atherosclerosis Risk in Communities (ARIC) study with no history of cardiovascular events and tumors and who came for their fourth visit (1997–1999) were included in the final analysis. Primary outcomes were recorded during the fourth visit; these included impaired lower extremity function, activities of daily living, and instrumental activities of daily living. A logistic regression model was used to test the associations between healthy lifestyle scores and functional impairment. The lifestyle score comprised six factors: healthy diet, moderate alcohol consumption, coffee consumption, physical activity, normal body weight, and no smoking. Results: Among the 10 602 participants with a median follow-up of 9 years, the prevalence rates of impaired lower extremity function, activities of daily living, and instrumental activities of daily living were 50.6%, 14.7%, and 21.6%, respectively. In the adjusted Cox regression model, participants with a healthy lifestyle score of 5 plus 6 had a significant lower risk of impaired lower extremity function (odds ratio=0.252, 95% confidence interval: 0.184–0.344, P<0.001), activities of daily living (odds ratio=0.201, 95% confidence interval: 0.106–0.380, P<0.001), and instrumental activities of daily living (odds ratio=0.274, 95% confidence interval: 0.168–0.449, P<0.001) than did participants with a score of 0. The association of healthy lifestyle scores with impaired activities of daily living and instrumental activities of daily living was stronger for individuals without diabetes than for those with it (P for interaction<0.05). This can be partly explained by the fact that the lowest risk of functional impairment among the participants with diabetes was associated with being overweight. Conclusion: Adherence to an overall healthy lifestyle was associated with a lower risk of physiological function limitation. This study highlights the importance of behavioral interventions in the prevention of disabilities.